Stress and influencing factors of public health and preventive medicine students in the post-pandemic period: a cross-sectional study in Changsha, China - Wang, Xiaofen; Zhang, Jiahui; Yang, Na; Zou, Miliang; He, Pingping (Frontiers in Public Health, 2023)
Little is known about the stress levels and associated factors of public health and preventive medicine students in the post-pandemic period. This study aims to investigate the stress levels of these students in the post-COVID-19 era and to determine the association of personal background, employment attitude, and psychological state with stress.: A cross-sectional survey was conducted in March 2023 among 620 public health and preventive medicine students from two universities in Changsha, China. The survey included demographic characteristics, employment attitudes, Perceived Stress Scale 10, General Anxiety Disorder 7, the University of California at Los Angeles Loneliness Scale 20, and the PTSD Checklist-Civilian Version. Two-sided t-tests and ANOVA tests were used to compare the differences in PSS scores among variables, and multiple hierarchical regression analysis was used to evaluate the associated factors with stress.The survey was completed by 504 students (mean age: 21.5± 2.6 years, 69.2% female). 24.8% of the students were screened for a high level of stress. 69.0% thought the epidemic positively impacted employment while 18.5% believed it had a negative impact. The results of regression analysis showed that older age (B=0.42, P=0.001), higher grade ( 1 =3.59, P<0.001, 2 =4.57, P<0.001), having internship experiences (B=1.16, P=0.006), having anti-epidemic experiences (B=1.77, P<0.001), believing that COVID-19 has a negative impact on employment (B=2.56, P<0.001), and having higher GAD scores (B=0.64, P<0.001) and UCLA scores (B=0.07, P=0.002) were significantly associated with high-stress levels. Conversely, being female (B=-1.64, P<0.001) and believing that the pandemic had a positive impact on employment (B=-1.98, P=0.001) were associated with low-stress levels. Conclusions: Public health and preventive medicine students in Changsha, China, experienced a high-stress level in the post-pandemic period, which was influenced by age, gender, grade, employment attitude, internship experience, anxiety, and loneliness. As one of the main guardians of the epidemic, these students should be given more attention and psychological interventions in the future.